2021
DOI: 10.1001/jamanetworkopen.2021.5493
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Studies Evaluating Spinal Manipulative Therapy and Infectious Disease and Immune System Outcomes

Abstract: Key Points Question Is spinal manipulative therapy associated with changes in the immune system? Findings In this systematic review of 13 studies comprising 795 participants, no clinical studies investigated the efficacy or effectiveness of spinal manipulative therapy in preventing or improving disease-specific outcomes among patients with infectious disease. Preliminary laboratory experiments indicated that spinal manipulative therapy may, in the short ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 54 publications
0
11
0
2
Order By: Relevance
“…The key to the prevention and control of infectious diseases lies in the cutting off of transmission routes, and the fever clinic is the main place for the prevention and control of infectious diseases, which can screen patients with infectious diseases at an early stage, give them isolation treatment in time, and cut off the transmission routes of infectious diseases [ 13 ]. However, some infectious diseases do not always present with febrile symptoms, and it is difficult to fully identify infected patients based on body temperature alone.…”
Section: Discussionmentioning
confidence: 99%
“…The key to the prevention and control of infectious diseases lies in the cutting off of transmission routes, and the fever clinic is the main place for the prevention and control of infectious diseases, which can screen patients with infectious diseases at an early stage, give them isolation treatment in time, and cut off the transmission routes of infectious diseases [ 13 ]. However, some infectious diseases do not always present with febrile symptoms, and it is difficult to fully identify infected patients based on body temperature alone.…”
Section: Discussionmentioning
confidence: 99%
“…Most chiropractors in our study identified recognised government agencies and professional bodies as their most trusted sources when seeking COVID-19 public health information. However, a smaller number of chiropractors have made claims on social media that chiropractic spinal manipulation reduces the adverse impact of COVID-19 [ 11 , 12 , 14 ], claims that appear to conflict with current clinical research evidence [ 51 , 52 ]. In response, leaders of the chiropractic research community [ 53 ], chiropractic regulatory bodies [ 15 , 16 ] and chiropractic professional associations [ 54 – 57 ] have made efforts to redress such claims within the profession.…”
Section: Discussionmentioning
confidence: 99%
“…Fact-checkers, health literacy guidelines, myth busters, checklists, and artificial intelligence can be useful tools to approach this goal [15,30]. Designing and conducting appropriate clinical studies to generate useful knowledge will support evidence-based decision making and contribute to flatten the infodemic curve [19,43]. Clear, concise communication and messaging allows decision-makers to take action based on correct interpretation of the data and avoids being misled, e.g., by low-quality data [14].…”
Section: Trans-impact Measuresmentioning
confidence: 99%